2012
DOI: 10.1246/cl.2012.1163
|View full text |Cite
|
Sign up to set email alerts
|

Striation Pattern of Impurity Particles in Charged Colloidal Crystals Formed by Stepwise Thermally Induced Crystallization

Abstract: Charged colloids form "crystal" structures, wherein the colloidal particles are regularly arranged as a result of strong electrostatic interparticle interactions. We have reported that silica colloids containing pyridine (Py) form colloidal crystals upon heating. Herein, we report that in Py + silica colloids including small numbers of fluorescent polystyrene (PS) particles, the PS particles are arranged in stripe patterns upon stepwise unidirectional crystallization when the temperature is increased by 1°C ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…When the heating temperature was varied in a stepwise manner, the impurities assembled in a striped pattern. 20 This was analogous to the striation patterns observed in most of the crystalline materials. 21 Colloidal silica exhibits unidirectional crystallization also due to diffusion of Py from the Py reservoir through semipermeable membranes.…”
Section: Controlled Crystallizationsupporting
confidence: 74%
“…When the heating temperature was varied in a stepwise manner, the impurities assembled in a striped pattern. 20 This was analogous to the striation patterns observed in most of the crystalline materials. 21 Colloidal silica exhibits unidirectional crystallization also due to diffusion of Py from the Py reservoir through semipermeable membranes.…”
Section: Controlled Crystallizationsupporting
confidence: 74%
“…Refining Due to Recrystallization and Zone Melting. We recently reported that impurity particles added to colloidal crystals were excluded from the crystals during crystal growth 33,34 and grain growth 34 Figure 9a shows micrographs that reveal the variation in the distribution of impurity particles with time. The crystal region was formed within t < 10 min and grew from left to right, as shown in Figure 9a.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that impurity particles added to colloidal crystals were excluded from the crystals during crystal growth , and grain growth processes. Here, we examined the exclusion of impurity particles during recrystallization and zone melting.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation